The Influence of Promotion through Instagram Social Media and Electronic Word of Mouth (eWOM) on Consumer Purchase Decisions of Kopi Ketje Panglima Polim in Bandar Lampung - Novitasari Novitasari; Arya Badaruddin (Journal Of Marketing and Technology Management, 2025)
This study aims to analyze the influence of promotion through Instagram social media and Electronic Word of Mouth (eWOM) on consumer purchase decisions at Kopi Ketje Panglima Polim in Bandar Lampung. This research employs a quantitative approach with a survey method. The sample consisted of 100 respondents who were customers of Kopi Ketje Panglima Polim, selected using purposive sampling. Data were analyzed using multiple linear regression with SPSS. The results show that promotion through Instagram has a positive and significant effect on purchase decisions. Similarly, eWOM has a positive and significant effect on purchase decisions. Simultaneously, Instagram promotion and eWOM significantly influence consumer purchase decisions. This study emphasizes that digital promotion strategies play an important role in increasing consumer buying interest and purchase decisions.